Pengaruh Deposito Mudharabah, Spread Bagi Hasil, Dan Tingkat Bagi Hasil Terhadap Pembiayaan Berbasis Bagi Hasil (Studi Empiris pada Bank Syariah di Indonesia) - PRAMONO, TEGUH, Dra. Mujiyati, M.Si (2017)
The purpose of this study was to investigate the influence of deposits mudaraba, spread revenue sharing, and the level of revenue sharing to finance revenue-sharing. This study uses empirical study on Islamic banking in Indonesia in the period of 2009 - 2014. The population in this study are all Islamic banking operations in Indonesia. Samples are five Islamic banks. The sample was taken by purposive sampling technique. The data obtained from the required financial statements of Islamic banks. Data were analyzed using classical assumption test and multiple regression analysis, t test, F test, and test the coefficient of determination. The results showed that: (1) the Deposit Mudharabah statistically positive effect on financing for results-based. The regression results obtained amounted to 19.533 tcount accepted at significance level of 5% and H1 accepted. This means increasing the funds raised from the public, then for results-based financing extended by Islamic banks will be increased; (2) Spread the results statistically significant negative effect on the results-based financing. The regression results obtained amounted to -14.384 tcount accepted at significance level of 5% and H2 is accepted. If the Islamic bank to apply for a high yield spreads to benefit or profit that is higher then the borrowers will turn to banks to apply for a low yield spreads; (3) The level for statistical results based financing to affect the results. The regression results obtained amounted to 8.360 tcount accepted at significance level of 5% and H3 accepted. Level of revenue sharing is an accepted part of customers (mudharib). The higher the level of revenue sharing that is applied then progressively increased public interest to apply for a loan to the Islamic banks; (4) Deposit mudaraba, spread for the results, and the level of revenue sharing simultaneously influence the results-based financing. The regression results obtained Fhitung 196.708 acceptable value at significance level of 5% and H4 accepted. This means that deposits mudaraba, spread revenue sharing, and the level of revenue sharing are all factors that affect the amount of financing revenue sharing Islamic bank distributed.